An evaluation of styles of IT support for marketing planning - Wilson, Hugh N.; McDonald, Malcolm (Emerald, 2001)
IT support for marketing planning can aid in the use of marketing tools, facilitate group planning, and support moves towards continuous planning based on a live marketing model of the business. But, amongst other factors, achieving these benefits depends on the style of support provided by the system. After a review of relevant decision support system (DSS) literature, describes here the findings relating to support style from a qualitative evaluation of a system named EXMAR. The findings support Little’s classic rules of “decision calculus”, such as the importance of ensuring that managers understand and can control the system, rather than the objective influenced by management science of prescribing an optimal recommendation. Also emphasises the role of systems in enhancing mutual understanding in a cross-functional planning team, and hence in building commitment to the resulting plan.